First report of Alexandrium taylori and Alexandrium peruvianum (Dinophyceae) in Malaysia waters - Po, T.L; Usup, G.; Chui, P.L; Ogata, T. (Elsevier Ltd, 2005)
The occurrence of Alexandrium taylori and Alexandrium peruvianum is reported for the first time in Malaysia waters. The Malaysian A. taylori isolates were pyriform in shape with a transdiameter range of 36–40 mm and a cell length range of 33– 37 mm. The first apical plate (10) was pentagonal with two distinctive anterior margins. No direct connection between 10 and the apical pore complex was observed. The posterior sulcal plate (S.p.) was large, elongated and oblique to the right with anterior projections. The ventral pore (vp) was relatively large and situated at a confluence point of 10, the second apical (20) and the fourth apical (40) plates. Cells of A. peruvianum were slightly anteriorly and posteriorly compressed. S.p. had an irregular pentagonal shape, with the anterior margin divided into 2 portions. 10 was boomerang-shaped with a large and truncated ventral pore in the middle right margin. The anterior right margin of 10 was straight. The sixth precingular plate (600) was wider than long. The anterior sulcal plate (S.a.) was triangular and lacked a left portion extension. In laboratory cultures, both A. taylori and A. peruvianum produced paralytic shellfish toxins, with GTX4 and GTX6 as the predominant toxin, respectively. This is the first report of PSP toxins production for both species as well as the occurrences in Malaysia waters.